Impact of Work Environment on the Productivity of Selected Teaching Personnel in College of Hospitality, Tourism, and Business Accountancy Management at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study analyzes the impacts of the work environment on a selected teachingpersonnel’s productivity. The objective of this study is to determine how the workenvironment affects the teaching personnel’s productivity and to come up with arecommendation based on the collected data.The fifty selected teaching personnel are from the courses of Bachelor of Science inHospitality Management (BSHM), Bachelor of Science in Tourism Management (BSTM),Bachelor of Science in Business Administration (BSBA), Bachelor of Science in OfficeAdministration (BSOA) and Bachelor of Science in Accountancy Information System (BSAIS)from the department of College of Hospitality, Tourism, Business, Accountancy andManagement (CHBAM) at Bestlink College of the Philippines. Based on the data gatheredon the respondents' demographic profiles, fifty-two percent of them are female.Based on the result of the collected data, it shows that work ambiance, a secured and safeworkplace, a good support system from colleagues, an organization that promotes goodvalues that lead to high performance, and an established technological system are the workenvironments that have a significant effect towards the productivity of teaching personnel. Italso shows that creating a learning material, reporting to work on time, being able to submitthe reports before the deadline, and having a strategic plan for presenting the lessons arethe effects of a good work environment on teaching personnel’s productivity.
Keywords: Business Administration